Lessening coke formation and boosting gasoline yield by incorporating scrap tire pyrolysis oil in the cracking conditions of an FCC unit. (15th November 2020) - Rodríguez, Elena; Izaddoust, Sepideh; Valecillos, José; Bilbao, Javier; Arandes, José M.; Castaño, Pedro; Epelde, Eva; Elordi, Gorka
Graphical abstract: Highlights: Effect of co-cracking scrap tire pyrolysis oil with vacuum gasoil in an FCC riser. Addition of STPO shows positive synergistic effects on gasoline yield and quality. STPO yields less coke, being more aliphatic, lighter, and located in the micropores. Two types of coke: soluble in the micropores and insoluble-structured in the matrix. Co-cracking of scrap tire pyrolysis oil may enhance the performance of the FCC unit. Abstract: We have studied the effect of adding scrap tire pyrolysis oil (STPO) as feed or co-feed in the cracking of vacuum gasoil (VGO) using a commercial equilibrated catalyst. The cracking experiments were performed in a laboratory scale fluid catalytic cracking (FCC) simulator using VGO, STPO, or a blend of the two (20 wt% of STPO), contact time = 6 s, catalyst/feed ratio = 5, and 530 °C. The composition of the different feeds has been correlated with the yield of products and the amount-location-nature of the deactivating species (coke). Our results indicate that adding STPO increases proportionally the gasoline yield, synergistically increase the yield of light cycle oil while uncooperatively decrease the yields of heavy cycle oil and coke. We further investigated the effect on coke formation, characterizing deeply the coked catalyst and coke. In fact, the coke deposited under the cracking of STPO is more aliphatic, lighter, and located in the micropores of the catalyst. The complete analysis of the coke fractions (soluble and insoluble) have lighted the peculiar chemistry of these species as a function of the type of feed used. The results point to a viable and economically attractive valorization route for discarded tires.